PHBV-graft-GMA via reactive extrusion and its use in PHBV/nanocellulose crystal composites - Zheng T.; Zhang Z.; Shukla S.; Agnihotri S.; Clemons C.M.; Pilla S. (My University, 2025)
Reactive extrusion was used for dicumyl peroxide (DCP)-initiated grafting of glycidyl methacrylate (GMA) to poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV). The effects of GMA and DCP content and their weight ratio on the GMA grafting percentage (GP%), the polymer melt viscosity, and the PHBV molecular weight were investigated. FTIR spectroscopy determined that the DCP did indeed initiate GMA grafting. However, the changes in both the zero-shear viscosity (η0) and the molecular weight suggested the existence of crosslinking products in the extruded polymers. A negative correlation between the degree of crystallinity (χc) of the PHBV-g-GMA and the GP% suggested the influence of chain branching on crystallinity. In addition, the GMA content was found as a key factor determining the GP%. The PHBV-g-GMA was used as a matrix polymer in cellulose nanocomposites to evaluate its effects on CNC dispersion and CNC-matrix adhesion relative to the unmodified PHBV matrix. The SEM images and the change in crystallization temperature suggested enhanced dispersion of CNC in a PHBV-g-GMA matrix. However, little increase in strength properties were found with CNC addition suggesting inadequate stress transfer between the matrix and CNCs. © 2018